Retraction: Biogenic amines as a diagnostic biomarker in inflammatory bowel diseases (European Journal of Health Research, 2025)
Title: Aminas Biógenas como biomarcador diagnóstico en enfermedades inflamatorias intestinalis [Aminas Biógenas como biomarcador diagnóstico en enfermedades inflamatorias intestinales]Authors: Juan A. López-Ayala, María Virtudes López-Ayala, Pablo Navarro-Hernández, Manuel Sánchez-Fernández.Indexing information: European Journal of Health Research - 2015, Vol. 1, Nº 3 (Págs.79-94)DOI: https://doi.org/10.30552/ejhr.v1i3.7
Keywords: retraction; ethics; authorship conflict